Production and Cleaning of Lattice Structures Used in the Space and Aerospace Industry with Metal Additive Manufacturing Method - Akbay, Ozgun Ceren; Bahce, Erkan; Uysal, Alper; Gezer, Ibrahim (SPRINGER, 2022)
Thanks to additive manufacturing, the use of lattice structures in aviation and space industry, especially heat exchangers, fuel nozzles and turbo machines located at the front of airplanes has increased. The production of computer-designed parts with the desired precision and geometry is important for concepts such as assembly, wear and surface properties. Problems encountered in selective laser melting (SLM) such as porosity, powder particle adhesions, affect assembly and surface properties. For this reason, cleaning is inevitable in sensitive systems used in the aerospace industry to have ready-to-use products after production or to prevent dust particles from breaking and causing problems in the workflow. To this purpose, chemical washing process was applied to improve the surface quality of the lattice structures and the healing effects of the acids used on the surfaces were investigated. In the experiment, nine lattice structures were produced from CoCr alloy and the effects of three different acid solutions prepared using hydrofluoric acid, nitric acid, sulfuric acid and hydrochloric acid on surface cleaning capacity were examined. The changes in the models immersed in the acid solution using the controlled immersion method for 180 seconds are presented comparatively. As a result of the experiment, it was seen that especially the solution containing hydrofluoric acid contributed to the improvement of the surface properties after production.
Keywords: chemical washing process; lattice structures in space and aerospace; metal additive manufacturing; SURFACE-ROUGHNESS; POROSITY; MICROSTRUCTURE; Materials Science